2003
DOI: 10.1111/j.1572-0241.2003.07303.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Levels of Chemokines in Esophageal Mucosa of Patients With Reflux Esophagitis

Abstract: Our results indicate that chemokines produced locally in the esophageal mucosa may be involved in the development and progression of RE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
94
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(99 citation statements)
references
References 24 publications
4
94
1
Order By: Relevance
“…21,22 Furthermore, an abnormal cytokine profile was observed in colonic primary fibroblast cells. 23 To support our in vitro findings of whether acid induces HB-EGF expression in fibroblast cells, we examined HB-EGF expression in biopsy specimens from the patients with reflux esophagitis as to show the in vivo evidence.…”
Section: Predominance Of Hb-egf In Subepithelial Fibroblasts Of Humanmentioning
confidence: 99%
“…21,22 Furthermore, an abnormal cytokine profile was observed in colonic primary fibroblast cells. 23 To support our in vitro findings of whether acid induces HB-EGF expression in fibroblast cells, we examined HB-EGF expression in biopsy specimens from the patients with reflux esophagitis as to show the in vivo evidence.…”
Section: Predominance Of Hb-egf In Subepithelial Fibroblasts Of Humanmentioning
confidence: 99%
“…IL-8 is a powerful chemoattractant and activator of leukocytes and other nonimmune cells. IL-8 levels in the esophagus correlate and increase with both endoscopic and histological disease severity (54,56,138). In a Japanese study of patients with nonerosive reflux disease (NERD) with minimal mucosal involvement, as determined by endoscopy, IL-8 mRNA levels were increased compared with NERD patients with no mucosal involvement and with controls (63).…”
Section: Inflammatory Mediators In the Inflamed Esophageal Mucosamentioning
confidence: 99%
“…IL-8 has been extensively studied in GERD and is expressed in high amounts in the affected mucosa of GERD patients (36,55,56,83,138). IL-8 is a powerful chemoattractant and activator of leukocytes and other nonimmune cells.…”
Section: Inflammatory Mediators In the Inflamed Esophageal Mucosamentioning
confidence: 99%
“…Of note, Fitzgerald et al [7] reported significantly higher expression levels of interleukin 8 (IL-8) messenger ribonucleic acid (mRNA) in patients with reflux esophagitis (RE), assessed by competitive reverse transcriptase polymerase chain reaction (RT-PCR), compared with subjects with non-inflamed or Barrett's esophagus. Studies from our laboratories have also demonstrated high IL-8 protein levels in esophageal biopsy samples of patients with erosive esophagitis by enzyme linked immunosorbent assay (ELISA) [8] . Furthermore, we also showed significantly high mucosal IL-8 production, which paralleled the endoscopic severity of RE [8] .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several studies have shown that mucosal immune and inflammatory responses, characterized by specific cytokine and chemokine profiles, may determine the diversity of esophageal phenotypes of GERD [7][8][9] . Of note, Fitzgerald et al [7] reported significantly higher expression levels of interleukin 8 (IL-8) messenger ribonucleic acid (mRNA) in patients with reflux esophagitis (RE), assessed by competitive reverse transcriptase polymerase chain reaction (RT-PCR), compared with subjects with non-inflamed or Barrett's esophagus.…”
Section: Introductionmentioning
confidence: 99%